Analysis Of Learning Management Providing Reinforcement On Student Learning Motivation In The Era Of Independent Learning - Rahayu, Sri; Widayati, Widayati; Ahmad Bachtiar Zen; Neng A’siah; Rostinah, Rostinah (Sean Institute, 2024)
The aim of this research is to examine learning management and determine whether, in the age of independent learning in junior high school, providing reinforcement by teachers has a beneficial impact on students' willingness to learn. The issue with this study is low student motivation for learning. The research was conducted quantitatively using product moment correlation analysis, involving 71 students of SMPN 111 Jakarta as samples. The data collection method used a scale of giving reinforcement by teachers and a scale of student learning motivation. The results of data analysis with product moment correlation analysis show that there is a positive relationship between giving reinforcement by teachers and student learning motivation. The correlation coefficient value rcount = 0.568 which is greater than rtable = 0.321, then it is concluded that there is a significant correlation between the provision of reinforcement by teachers to student learning motivation.